A Retrospective Audit Of Biojet® Prostate Fusion Biopsies Amongst Patients Seen In A High-Volume Private Referral Centre In Cape Town Between January 2017 And April 2020 - Patel, Bhavinkumar (Division of General Surgery, 2024)
Introduction: The field of prostate cancer has seen a dramatic change in its approach to diagnosis, from the advent of PSA in the 1980s to the transrectal ultrasound guided 12 core biopsies with a false negative rate of approximately 30%. Recent advances in this field involve fusing MRI images with real-time ultrasound images to guide the surgeon. The aim of the study was to evaluate the performance of Biojet® prostate fusion biopsy system in a high-volume private referral centre. Methods: Retrospective observational audit of men who presented to a private urology practice in Cape Town for Biojet® prostate fusion biopsy based on clinical suspicion for prostate cancer. Data were collected as per the recommendations of the Standards of Reporting for MRI-targeted Biopsy Studies (START) of the Prostate group and anonymously entered onto a Redcap database. Results: The median age of the patient population was 64 (SD 9.124) years. The median PSA level was 6.5 ng/ml (IQR- 4.7). Most patients (78/135) had a clinical stage of T1c (57%). In the biopsy naïve group, a total of 103 PIRADS lesions were identified. Amongst the PIRADS 3 lesions 15/28 lesions (53%) had a positive cancer diagnosis. Of the PIRADS 4 lesions 37/60 lesions (62%) had a positive cancer diagnosis and in the PIRADS 5 group 13/15 lesions (87%) had a positive cancer diagnosis. 21 of the 42 men (50%) with a previous negative prostate biopsy had a positive cancer diagnosis using the Biojet® prostate fusion biopsy. Conclusion: In this study the Biojet® prostate fusion biopsy performed similar to other international studies however the pickup rate of cancer in those who had a previous negative biopsy was higher than those seen in the other global studies.